Pertanggung Jawaban Pidana Pelatih Pencak Silat Terhadap Anggotanya yang Meninggal Perspektif Hukum Positif dan Hukum Pidana Islam: Criminal Liability of Pencak Silat Trainers for the Death of Their Members: A Perspective of Positive Law and Islamic Criminal Law - Ilham Khoirul Ummah (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Criminal liability of a pencak silat coach for the death of a student is an issue that frequently arises within pencak silat organizations,particularly when incidents result in fatalities. Such cases fall under the category of negligence when viewed from the perspective of the positive legal system, specifically under Article 359 of the Indonesian Criminal Code (KUHP). From the perspective of Islamic criminal law (fiqh jinayah), the applicable punishment is diyat (compensation to the victim’s family). This study addresses three main questions: (1) What is the form of criminal liability for a coach whose actions result in the death of a student, from the perspective of positive law?(2) What is the form of criminal liability for such a coach, from the perspective of fiqh jinayah?(3) What are the similarities and differences in the criminal liability of a pencak silat coach causing the death of a student, when viewed from both positive law and fiqh jinayah? The objectives of this research are: (1) To analyze the form of criminal liability of a pencak silat coach whose actions result in the death of a member, from the perspective of positive law.(2) To examine the same matter from the viewpoint of fiqh jinayah.(3) To compare the criminal liability of a pencak silat coach causing the death of a member in bothfiqh jinayah and positive law. This study employs a normative legal research method, meaning it relies on obtaining data and information relevant to the legal issue under discussion through a literature review. Pertanggung jawaban pidana pelatih pencak silat terhadap anggotanya yang meninggal merupakan permasalahan yang seringterjadi di kalangan organisasi pencak silat yang sampai ke titik meninggal, faktor ini masuk dalam kategori kelalaian jika dilihat darisistem hukum positif menggunakan pasal 359 KUHP, jika dilihat dari sistem hukum pidana islam hukumannya berupa diyat, (1)Bagaimana bentuk pertanggung jawaban pidana terhadap pelatih yang menyebabkan kematian kepada siswanya ditinjau perspektifhukum positif ? (2) Bagaimana bentuk pertanggung jawaban pidana terhadap pelatih yang menyebabkan kematian kepada siswanyaditinjau perspektif Fiqh Jinayah? (3) Bagaimana komparasi persamaan dan perbedaan pertanggung jawaban pelatih pencak silatyang menyebabkan kematian di tinjau dari hukum positif dan fiqh jinayah? Tujuan dari penelitian ini adalah : (1) Untuk menganalisabentuk pertanggung jawaban pidana terhadap pelatih pencak silat yang menyebabkan kematian kepada anggotanya dalam prespektif Hukum Positif. (2) Untuk mengetahui pelatih yang menyebabkan kematian terhadap anggotanya dalam pandangan Fiqh Jinayah. (3) Untuk mengkomparasi pertanggung jawaban pelatih pencak silat yang menyebabkan kematian terhadap anggotanya di tinjau dari fiqh jinayah dan hukum positif. Penelitian ini merupakan hukum normatif dengan artian penelitian yang dilakukan dengan cara mendapatkan data atau informasi yang sesuai dengan isu hukum yang dibahas dengan kajian pustaka.